2021
DOI: 10.1016/j.abrep.2021.100365
|View full text |Cite
|
Sign up to set email alerts
|

Does a 7-day restriction on the use of social media improve cognitive functioning and emotional well-being? Results from a randomized controlled trial

Abstract: Highlights We compared a 10% vs. 50% reduction in social media screen time in a RCT. The intervention had no effect on multiple indicators of attention and wellbeing. Self-control, impulsivity and FoMO did not moderate the relationships. Participants reported improved attention, but behavioral attention did not improve. Overall, a more severe screen time reduction intervention does not appear more beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 72 publications
0
19
1
Order By: Relevance
“…One feature that may explain the differences in these findings is the length of abstinence, with the longer-term studies (e.g., Hunt et al, 2018Hunt et al, , 2021 reporting greater improvements than studies using shortened timeframes (e.g., Przybylski et al, 2021;van Wezel et al, 2021). In fact, Hall et al (2019) found that reducing social media use can have multiple effects on wellbeing.…”
mentioning
confidence: 99%
“…One feature that may explain the differences in these findings is the length of abstinence, with the longer-term studies (e.g., Hunt et al, 2018Hunt et al, , 2021 reporting greater improvements than studies using shortened timeframes (e.g., Przybylski et al, 2021;van Wezel et al, 2021). In fact, Hall et al (2019) found that reducing social media use can have multiple effects on wellbeing.…”
mentioning
confidence: 99%
“…To the best of our knowledge, no other trials have investigated the impact of limiting overall recreational digital screen use on perceived mental well-being and mood. Some trials have investigated the short-term effects of limiting social media engagement on mental well-being and shown mixed results 13 17 . A key difference between previous trials and our trial is the high level of intervention compliance observed in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…While the findings based on observational studies may be affected by uncontrolled confounding or information bias caused by use of self-reported screen use 10 , 12 , another major limitation is the possibility of reverse causation—that is, that recreational screen use is increased as a consequence of mental health issues 8 . Recently, a few experimental studies have investigated the short-term effects of reducing social media use (not overall recreational screen use) on mental health 13 17 . However, evidence is still inconclusive primarily due to methodological limitations such as lack of objective assessment of intervention compliance or non-compliance to the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 17 authors were contacted for data due to insufficient information provided in the reports to calculate effect sizes. Of those, eight provided the requested data (Gobin et al, 2022; Hall et al, 2021; Hinsch & Sheldon, 2013; Hunt et al, 2018, 2021; Mosquera et al, 2020; Turel et al, 2018; van Wezel et al, 2021), leaving ten studies where effect sizes could not be calculated. Those studies with insufficient data to enable the calculation of effect sizes were included in the narrative synthesis of findings.…”
Section: Methodsmentioning
confidence: 99%